Production of exoctic fragments by photofission process combined with stopping gas cell at ELI-NP facility - Phan , Viet Cuong; BALABANSKI, DIMITER L.; CONSTANTIN, PAUL; Tran , Duc Thiep; Nguyen , The Vinh; Bui , Minh Hue (Nuclear Science and Technology, 2015)
Extreme Light Infrastructure Nuclear Physics (ELI-NP) facility is being built at Bucharest-Magurele, which then allow us to do research about nuclear physics using a new set of research tools: high power laser system and high brilliance gamma beams. One of day-one experiment proposed at this facility is to study the photofission of actinide by the high-intensity gamma beam through measurement of mass and beta decay. In addition, ternary fission will be also studied. In particular, the measurements of exotic neutron-rich nuclei produced by photofission, especially isotopes of refractory elements, is of great interest and requires the development of an IGISOL-type (Ion guide isotope separation online). In this report, we will present benchmark simulation of photofission rate and rates of related background processes.